Green diesel and its role as a drop-in renewable diesel alternative to FAME-based biodiesel - Muhammad Latifur Rochman; Nurkholis Hamidi; Femiana Gapsari; Winarto Winarto (Universitas Muhammadiyah Magelang, 2025)
Fatty acid methyl ester (FAME) biodiesel has been widely adopted as a renewable alternative to fossil diesel due to its relatively simple production process and established blending frameworks. Nevertheless, intrinsic limitations associated with its oxygenated ester structure such as oxidative instability, hygroscopicity, cold-flow constraints, and restricted blend ratios, continue to limit its long-term suitability for advanced diesel engines and fuel systems. Green diesel, also known as renewable diesel, is a hydrocarbon fuel produced from renewable and waste lipid feedstocks through catalytic deoxygenation pathways, yielding paraffinic hydrocarbons that closely resemble conventional petroleum diesel.